EN TORNO AL CAMPO SEMÁNTICO DEL SENTIMIENTO EN LA ILIADA - Carrillo Vera, Ana Dolores (Myrtia, 1987)
With this paper we try to demonstrate the importance of the hypotheses of the Structural Linguistics in the study of the work by Homer. Here we study the semantic field in the context of the adjective, by which we observe the existence of a perfectly structured, a system wellknown to Homer, as we have demonstrated in this article.